Validating content of sentence variety checklist for ESL writing - Abdullah, Liza; Jusoh, Zailani (Human Resource Management Academic Research Society (HRMARS), 2017)
Sentence variety is a fundamental aspect in writing to avoid stereotypes, thus making writing more interesting. It is taken more seriously when it comes to assessment, compared to teaching. Students seem to be reluctant to learn more about it, and teachers are reluctant to teach (Saddler, 2007). With the intervention of sentence variety checklist (SVC) to promote sentence variety, this study investigated the validity of items in the SVC adapted from Langan (1993) to be justified, prior to its use in the ESL writing classroom. Five ESL teachers who are the writing experts and have been teaching writing for more than 15 years in a public university in Malaysia responded to the questionnaire of 14 items rephrased from the items in the checklist and one open-ended question for further suggestions. The data were analysed by computing Content Validity Index (CVI) using ratings of content item relevance by the writing experts. The results revealed that out of 14 items, 12 items were rated as highly relevant while the other two were still relevant. In addition, passive voice appeared to be another item suggested to be included in the checklist in the efforts to boost students’ writing performance.